The declining effect of sibling size on children's education in Costa Rica - Li, Jing (2014)
Background: Costa Rica experienced a dramatic fertility decline in the 1960s and 1970s. The same period saw substantial improvement in children’s educational attainment in Costa Rica. This correlation is consistent with household-level quantity-quality tradeoffs, but prior research on quantity-quality tradeoff magnitudes is mixed, and little research has estimated quantity-quality tradeoff behaviors in Latin America. Objective: This study explores one dimension of the potential demographic dividend from the fertility decline: the extent to which it was accompanied by quantity-quality tradeoffs leading to higher educational attainment. Specifically, we provide the first estimate of quantity-quality tradeoffs in Costa Rica, analyzing the increase in secondary school attendance among Costa Rican children as the number of siblings decreases. Furthermore, we advance the literature by exploring how that tradeoff has changed over time. Methods: We use 1984 and 2000 Costa Rican census data as well as survey data from the Costa Rican Longevity and Healthy Aging Study (CRELES). To address endogenous family size, the analysis uses an instrumental variable strategy based on the gender of the first two children to identify the causal relationship between number of siblings and children’s education. Results: We find that, among our earlier cohorts, having fewer siblings is associated with a significantly higher probability of having attended at least one year of secondary school, particularly among girls. The effect is stronger after we account for the endogeneity of number of children born by the mother. For birth cohorts after 1980 this relationship largely disappears. Conclusions: This study provides strong evidence for a declining quantity-quality (Q-Q) tradeoff in Costa Rica. This result suggests one potential explanation for the heterogeneous findings in prior studies elsewhere, but more work will be required to understand why such tradeoffs might vary across time and context.